HUBUNGAN POLA ASUH ORANG TUA DENGAN KEMANDIRIAN SISWA DI SMPIT AL-KHAIRIYYAH - Aldi Mugia; Santi Lisnawati; Ikhwan Hamdani (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
This research is motivated by student behavior that reflects a lack of self-confidence and dependence on teachers or parents, which poses a problem in terms of student independence. Therefore, this study aims to determine the forms of parenting styles applied to students, assess the level of student independence, and analyze the relationship between parenting styles and student independence. This study uses a quantitative correlational method. The data collection was conducted using a parenting style scale based on Hurlock’s theory and a student independence scale based on Steinberg’s theory. The researcher aims to explore the relationship between parenting styles and student independence at SMPIT Al-Khairiyyah in a thorough and comprehensive manner. Data were collected through questionnaires using a survey method. The data were analyzed using SPSS version 26.0, with the hypothesis tested through Pearson Product-Moment correlation analysis. Based on the results of this study, it can be concluded that there is a positive relationship between parenting styles and student independence. This is statistically proven by a significance value (2-tailed) of 0.000 < 0.05 and a correlation coefficient of 0.661 A coefficient of determination of 0.437 indicates that 43.7% of the variance in student independence can be explained by the parenting style variable, suggesting a strong and significant relationship between the two variables.